تہذیبِ نفس کے اسلامی اصول:تحقیقی و تجزیاتی مطالعہ (Al-Qamar, 2023)
It is a bit difficult to determine the principles of purification of soul in this way, because its principles are numerous. However, there is one thing in common among the excess of principles, that among the principles that are detailed, there are also summary principles. Due to which, the principles of purification of soul Familiarity with rules and regulations is possible. Self refers to that force which is the source of thoughts. Self is the source of thoughts and feelings. Therefore, the thoughts of goodness and evil also begin from here. The first thought arises in the self of man. Later, the same thought takes the form of intention and actions are created by intention. It is as if there is no idea, then no action is created by man. The self exists as a test and trial in the universe. It is always ready to mislead a person. If a person follows the idea created in the mind, then he will be caught in the net of the self, while if he follows the decision of the heart, then common sense will be included in it. Due to which a person will be inclined to do good instead of evil. Self-improvement refers to the immaterial source of thoughts in a person, i.e., purifying the self from bad morals and sins and making oneself a manifestation of pure morals. Self-improvement. Among the principles of repentance, fear of God, asceticism, patience, gratitude, sincerity, trust, love, education, contentment and fear of death are mentioned in this article.
Keywords: Quran; Sunnah; Shari'ah; Soul; Purification of Sou; Mannerliness